Praññʻ tvaṅʻʺ Ññī ññvatʻ reʺ ʼA kraṃ peʺ ʼA phvaiʹ cā tanʻʺ ʼa poʻ ve phanʻ khyakʻ - Sinʻʺ Phe Mraṅʻʹ, 1914-1978 (Lha Myuiʺ Cā pe, 1969)
Criticism on the report of the Praññʻ tvaṅʻʺ Ññī ññvatʻ reʺ ʼA kraṃ peʺ ʼA phvaiʹ, national integration advisory committee, to the government of Burma on central planning.